Metabolic pathways of T-2 toxin - Dohnal, Vlastimil; Ježková, Alena; Jun, Daniel; Kuča, Kamil (Current drug metabolism, 2008)
Among the naturally-occurring trichothecenes found in food and feed, T-2 toxin is the most potent and toxic mycotoxin. After ingestion of T-2 toxin into the organism, it is processed and eliminated. Some metabolites of this trichothecene are equally toxic or slightly more toxic than T-2 itself, and therefore, the metabolic fate of T-2 toxin has been of great concern. The main reactions in trichothecene metabolism are hydrolysis, hydroxylation and deep oxidation. Typical metabolites of T-2 toxin in an organism are HT-2 toxin, T-2-triol, T-2-tetraol, 3'-hydroxy-T-2, and 3'-hydroxy-HT-2 toxin. There are significant differences in the metabolic pathways of T-2 toxin between ruminants and non-ruminants. Ruminants have been more resistant to the adverse effects of T-2 toxin due to microbial degradation within rumen microorganisms. Some plant species are resistant to T-2 toxin, while others are capable of its intake and metabolisation.
Keywords: Bacteria; biotransformace; Rumen; Hydrolysis; zvířata; Hydroxylation; financování organizované; T-2 Toxin; sladká voda; hydroxylace; Fungi; hydrolýza; T-2 toxin; houby; Financing, Organized; Soil Microbiology; Plants; půdní mikrobiologie; Biotransformation; bachor; Oxidation-Reduction; Fresh Water; Animals; oxidace-redukce; rostliny